Case Report: Meningoencephalitis With Thrombotic Occlusive Vasculopathy in a Young EBV-Naïve Boy Is Associated With a Novel SH2D1A Mutation - Steininger, Jolanda; Rossmanith, Raphael; Geier, Christoph B.; Leiss-Piller, Alexander; Thonhauser, Lukas; Weiss, Simone; Hainfellner, Johannes A.; Freilinger, Michael; Schmidt, Wolfgang M.; Eibl, Martha M.; Wolf, Hermann M. (Frontiers in Immunology, 2021)
X-linked lymphoproliferative disease (XLP1) is a combined immunodeficiency characterized by severe immune dysregulation caused by mutations in the SH2D1A/SAP gene. Loss or dysfunction of SH2D1A is associated with the inability in clearing Epstein-Barr-Virus (EBV) infections. Clinical manifestation is diverse and ranges from life-threatening hemophagocytic lymphohistiocytosis (HLH) and fulminant infectious mononucleosis (FIM) to lymphoma and antibody deficiency. Rare manifestations include aplastic anemia, chronic gastritis and vasculitis. Herein, we describe the case of a previously healthy eight-year old boy diagnosed with XLP1 presenting with acute non-EBV acute meningoencephalitis with thrombotic occlusive vasculopathy. The patient developed multiple cerebral aneurysms leading to repeated intracerebral hemorrhage and severe cerebral damage. Immunological examination was initiated after development of a susceptibility to infections with recurrent bronchitis and one episode of severe pneumonia and showed antibody deficiency with pronounced IgG1-3-4 subclass deficiency. We could identify a novel hemizygous SH2D1A point mutation affecting the start codon. Basal levels of SAP protein seemed to be detectable in CD8+ and CD4+ T- and CD56+ NK-cells of the patient what indicated an incomplete absence of SAP. In conclusion, we could demonstrate a novel SH2D1A mutation leading to deficient SAP protein expression and a rare clinical phenotype of non-EBV associated acute meningoencephalitis with thrombotic occlusive vasculopathy.